Correlações entre medidas ultra-sonográficas do coração e o déficit de hemoglobina em fetos de gestantes isoimunizadas - Marilia Zicker Hanan (2007)
Introduction: the hemolytic disease of the fetus and the newborn secondary to maternal sensitization, represents the most common cause of anemia that can be avoided. In the management and treatment of the fetal disease it is necessary to detect the degree of fetal anemia. The objective of the current approach using noninvasive tests is to reduce the risk and the worsening of maternal sensitization associated with invasive procedures. Objective: to verify the correlation between echographic cardiac measurements assessed and fetal hemoglobin deficit ofisoimmunized pregnant women. Patients and methods: A prospective crosssectional study was carried out in 60 fetuses between 21 and 35 weeks of 56 Rh negative women with red blood cells isoimmunization comprising 139 procedures. Before cordocentesis and blood sample, cardiac measurements of biventricular outer diameter (BVOD) and of atrioventricular diameter (AVD) were obtained in a four chamber view at end-diastole using real-time ultrasound and M-mode assessment and cardiac circumference (CC) was calculated. These measurements were adjusted to femur length (FL). The equipments used were USSONOACE 8800 and 8000 (MEDSOM®) with a 3,5 Mhz transducer. Hemoglobin concentration was measured with spectrophotometry in the HEMOCUE® device and hemoglobin deficit (Hb Def) was calculated based on Nicolaides normal reference range (NICOLAIDES et al., 1988b). No anemia was defined when there wasnt a Hb Def or a Hb Def = 2g/dL. Mild anemia was defined as a Hb Def > 2g/dL and < 5 g/dL, moderate anemia as a Hb Def = 5 g/dL and = 7 g/dL and severe anemia a Hb Def > 7g/dL. Results: no anemia was present in 43% of thefetuses, mild anemia in 30%, moderate anemia in 14% and severe anemia in 14%. Cardiac measurements assessed and FL ratio showed positive (r=0,344 to BVOD/FL; r=0,237 to AVD/FL and r=0,325 to CC/FL) significative (p<0,05) correlations with fetal Hb Def The values of cardiac measurements assessed and FL ratio were similar among previously transfused and no transfused fetuses. Sensitivity and specificity in the diagnosis of moderate and severe anemia were respectively, 71,7% and 66,3% to BVOD/FL, 65,8% and 62,4% to AVD/FL and 73,7% and 60,4% to CC/FL. Conclusions: echographic cardiac measurements assessed on fetus of isoimmunized pregnant women showed positive correlationswith fetal hemoglobin deficit. The findings suggest that these measurements may be used - associated or not to others markers - as a noninvasive method of fetal anemia diagnosis in these pregnant women.